A Study on Platform's New Strategy in Media 2.0 Era - Based on “Keystone” concept & Google case - Minzheong Song (International Telecommunications Society (ITS), 2010)
The purpose of this paper is to suggest a new strategy of the platform in Media 2.0 era. This goal is approached by firstly examining conceptual change of the platform strategy from mass media world (Media 1.0) to micro media world (Media 2.0). Then, it will discuss "Keystone" strategy by Iansiti & Levien (2004) who introduced four different types of platform and will give an example, Google. The data shows, how Google's keystone strategy could be successfully accomplished with three sources for value creation, revelation, aggregation and plasticity, and how healthy it is in terms of productivity, robustness, and niche creation. Finally, an applicable framework to Media 2.0 will be constructed on the basis sources for value creation and "Keystone" capabilities of ecosystem management. Three main parts of the keystone strategy are the openness, synchronization, and mass customization focus.
Keywords: 330; Media platform; Keystone; ecosystem